Pemanfaatan Kulit Buah Jeruk Nipis (Citrus aurantiifolia) Sebagai Pembasmi Jentik Nyamuk di Desa Suci, Kecamatan Panti, Kabupaten Jember - Syehan, Naomi Azka; Aprillia, Dena; Wahyu, Laila Muflia; Zahira, Farah Tiara; Nurmusfiroh, Rizqi Faza; Fauziah, Maya A’ida; Kusnadi, Maulidya Dzikiria; Kamalia, Rahmania Addieni (UNEJ e-Proceeding, 2023)
Background: Dengue Hemorrhagic Fever is an acute febrile disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti vector. Along with efforts to reduce the incidence of Dengue Hemorrhagic Fever, it is necessary to control the Aedes aegypti vector through natural insecticides that are environmentally friendly by utilizing lime peel extract in the form of essential oils. This community service activity aims to educate the people of Suci Village, Panti District, Jember Regency, regarding the formulation for using natural mosquitoes from lime peel in the form of essential oils. Method: This community service activity has several methods, namely lectures, questions, and answers, and filling in pre-test and post-test sheets to measure community knowledge regarding lime peel products. Conclusion: The application of this product is expected to effectively kill Aedes aegypti larvae so that the incidence of Dengue Hemorrhagic Fever can be minimized. After conducting education, it can be seen that public knowledge has increased regarding using natural anti-mosquito formulations from lime peel. The increased pre-test to post-test results evidence this.Keywords: dengue hemorrhagic fever, lime peel, mosquito larvae, repellent